THE DEVIATION OF WORDS ASPECTS AND SENTENCES AMONG STUDENTS’ SPEECH - I Putu Mas Dewantara (Jurnal Pendidikan dan Pengajaran, 2017)
This study was aimed at describing the misuse of spoken Bahasa Indonesia by students of Universitas Pendidikan Ganesha in terms of words and sentences. This study was descriptive qualitative research. Sources of data in this study were students taking Bahasa Indonesia subject as a part of Personality Development Course. Data collection method used was observation and documentation. Three stages of data analysis were implemented for this study, namely: data reduction, data presentation, and inference and verification. Techniques used in checking the validity of the data and the data saturation is the persistence of observation and data triangulation. The results of this study were (1) the misuse of spoken Bahasa Indonesia seen from word aspects includes (a) the misuse in pronunciation (phonology); (B) the misuse of words (lexical); (C) variations of word; and (d) the misuse of word formation (morphology); (2) the misuse of spoken Bahasa Indonesia seen from sentence aspects includes (a) contamination sentences; (B) pleonastic sentences; (C) ambiguous sentences; and (e) illogical sentences. The results of this study can be taken into consideration in the selection of teaching materials for students.